The Pattern of Social Changes in the Samin Community and Its Influencing Factors - Muhamad Arif; Abdul Ghofur; Dhanang Respati Puguh (IHiS (Indonesian Historical Studies), 2021)
In general, social changes occurred progressively, but it is not happened in the Samin community. This article aims to analyze the social changes in the Samin community in Tapelan Village and its influencing factors. The research was conducted in Tapelan Village, Ngraho District, Bojonegoro, using a qualitative and descriptive approach. There are two important findings in this study. First, there is a regressive pattern of social change in the Samin community during the colonial period, with the Dutch colonialists taking over teak forests in 1890, forcing the Samin community to leave the forest, becoming a closed society, and developing a unique tradition. Second, there is a progressive pattern of social change in the Samin community during the independence era after rediscovering their identity as an open and adaptive society, with Islamic dakwah as the main driver of social change.